A method for preparing a membrane electrode for water electrolysis
By setting the carrier layer between the transfer base and the catalytic layer, the problem of unstable quality of catalytic layer and low finished product ratio are solved, and the high -quality preparation and large -scale production of electrolytic water film electrodes are realized.
Patent Information
- Application Number
- CN202211134131.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-09-15
AI Technical Summary
The quality of the catalytic layer produced by the existing transfer method is unstable and the yield is low, which limits the large-scale production of membrane electrodes for electrolytic water.
Set the carrier layer between the transfer base and the catalytic layer. Through the setting of the carrier layer, the problem of incomplete transmission caused by the catalytic layer due to adherence to the transparent base, thereby stabilizing the quality of the catalytic layer, transferring the transfer of the catalytic layer, transferring the transfer of the catalytic layer, transferring the transfer of the catalytic layer, transferring the transfer of the catalyst. High efficiency.
Through the use of the carrier layer, the complete transfer of the catalytic layer is realized, and the load uniformity and the rate of finished product rate of the catalytic layer are improved.
Smart Images

Figure CN115505947B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis, and in particular to a method for preparing a membrane electrode for water electrolysis. Background Art
[0002] Hydrogen energy is a new energy source with broad application prospects. It has the advantages of high energy density, renewability and zero carbon emissions, and is expected to replace fossil energy in future development, thereby ensuring the sustainable supply of energy. The water electrolysis hydrogen production technology can realize the direct conversion from electrical energy to hydrogen energy, and can be combined with renewable energy to form an economical, efficient and environmentally optimized hydrogen production industry.
[0003] Solid polymer electrolyte (SPE) water electrolysis technology has the advantages of small equipment size, fast startup, high current density, and high gas purity. It is currently the key research direction of water electrolysis technology. SPE water electrolysis technology uses proton exchange membrane (PEM) as a solid electrolyte to replace the diaphragm and strong alkaline electrolyte in traditional alkaline water electrolysis technology, which not only improves the ion transfer efficiency, but also avoids the corrosion of strong alkali to the equipment. In SPE water electrolysis technology, the membrane electrode, as a composite structure with catalytic, conductive and proton transfer functions, is the core component of the entire electrolyzer system. The existing membrane electrode structure includes PEM and a cathode catalyst layer and an anode catalyst layer located on both sides.
[0004] At present, the commonly used processes for loading the catalyst layer on PEM include ultrasonic spraying and transfer printing. Among them, the ultrasonic spraying method directly sprays the catalyst slurry on the surface of PEM. Although it can achieve uniform dispersion of the catalyst slurry, there are problems such as swelling of the proton exchange membrane, low catalyst utilization rate, and large environmental pollution, which makes it difficult to achieve large-scale mass production; the transfer printing method is to first coat the catalyst on the surface of the transfer substrate and then transfer it to the PEM. It has the advantages of high yield, no swelling, and low pollution, but when the catalyst slurry is coated on the transfer substrate, it is easy to have uneven catalyst loading, and because there is a certain adhesion between the catalyst layer and the transfer substrate, the catalyst layer transfer is often incomplete or even fails during the transfer process. The above two situations will lead to unstable quality of the final catalyst layer and low yield, thereby limiting the large-scale production of membrane electrodes for water electrolysis. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing a membrane electrode for water electrolysis, aiming to solve the problems of unstable quality and low yield of the catalytic layer prepared by the existing transfer method.
[0006] To achieve the above object, the present invention provides a method for preparing a membrane electrode for water electrolysis, the preparation method comprising the following steps:
[0007] Disposing a first carrier layer on an upper surface of a transfer substrate;
[0008] Disposing a second carrier layer on the upper surface of another transfer substrate;
[0009] Disposing a cathode catalyst layer on the first carrier layer;
[0010] Disposing an anode catalyst layer on the second carrier layer;
[0011] The cathode catalyst layer and the anode catalyst layer are respectively placed on both sides of the proton exchange membrane, and the cathode catalyst layer is in contact with the proton exchange membrane, and the anode catalyst layer is in contact with the proton exchange membrane, and subjected to hot pressing treatment to obtain a composite membrane;
[0012] placing the composite membrane in a solvent to dissolve the first carrier layer and the second carrier layer in the solvent to obtain a membrane electrode for water electrolysis;
[0013] Wherein, the material of the first carrier layer includes a high molecular polymer, and the material of the second carrier layer includes a high molecular polymer.
[0014] Optionally, the material of the transfer substrate includes at least one of polytetrafluoroethylene, fluorinated ethylene propylene copolymer, perfluoroalkoxy copolymer, polyvinylidene fluoride and ethylene-tetrafluoroethylene copolymer.
[0015] Optionally, the material of the first carrier layer includes at least one of polyvinyl alcohol, polyethylene oxide, polymethylpyrrolidone, polyacrylamide and polyacrylic acid; and / or,
[0016] The material of the second carrier layer includes at least one of polyvinyl alcohol, polyethylene oxide, polymethyl pyrrolidone, polyacrylamide and polyacrylic acid.
[0017] Optionally, the step of providing a cathode catalyst layer on the first carrier layer comprises:
[0018] The cathode catalyst slurry is coated on the upper surface of the first carrier layer and then dried to obtain a cathode catalyst layer, wherein the cathode catalyst slurry includes a cathode catalyst, a dispersant and a binder.
[0019] Optionally, the cathode catalyst comprises Pt / C; and / or,
[0020] The dispersant comprises at least one of water, ethanol, isopropanol and n-propanol; and / or,
[0021] The drying temperature of the drying is 50 to 90° C.; and / or,
[0022] The cathode catalyst slurry may be applied by any one of blade coating, brush coating and screen printing.
[0023] Optionally, the cathode catalyst loading of the cathode catalyst layer is 0.5 to 5 mg·cm -2 .
[0024] Optionally, the step of providing an anode catalyst layer on the second carrier layer comprises:
[0025] The cathode catalyst slurry is coated on the upper surface of the first carrier layer and dried to obtain a cathode catalyst layer, wherein the anode catalyst slurry includes an anode catalyst, a dispersant and a binder.
[0026] Optionally, the anode catalyst comprises iridium dioxide; and / or,
[0027] The dispersant comprises at least one of water, ethanol, isopropanol and n-propanol; and / or,
[0028] The drying temperature of the drying is 50 to 90° C.; and / or,
[0029] The method of applying the anode catalyst slurry includes any one of blade coating, brush coating and screen printing.
[0030] Optionally, the anode catalyst loading of the anode catalyst layer is 0.5 to 5 mg·cm -2 .
[0031] Optionally, in the hot pressing treatment step, the hot pressing temperature is 90 to 140° C., the hot pressing pressure is 0.2 to 5.0 MPa, and the hot pressing time is 1 to 10 min.
[0032] In the technical solution provided by the present invention, a carrier layer is arranged between the transfer substrate and the catalyst layer. By the arrangement of the carrier layer, the problem of incomplete transfer caused by the catalyst layer adhering to the transfer substrate is avoided, so that the quality of the catalyst layer is stable and the transfer efficiency is high; the material of the carrier layer includes a high molecular polymer, so that the carrier layer has a larger surface tension than the transfer substrate, so that the carrier layer is more easily infiltrated by the catalyst slurry, so that the load uniformity of the catalyst layer is good; in addition, the carrier layer can be removed in the subsequent processing process, will not interfere with the performance of the membrane electrode, and the removal method is simple. Therefore, the membrane electrode for electrolysis of water obtained by the preparation method provided by the present invention has good performance, long service life, stable quality, high yield rate, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 A schematic flow chart of an embodiment of a method for preparing a membrane electrode for water electrolysis provided by the present invention;
[0035] Figure 2 This is a scanning electron microscope image of the membrane electrode prepared in Example 1 of the present invention;
[0036] Figure 3 This is a comparison diagram of the actual transfer effect during the membrane electrode preparation process in Example 1 of the present invention and Comparative Example 1;
[0037] Figure 4 This is a performance test result diagram of the membrane electrode prepared in Example 1 of the present invention and Comparative Example 1.
[0038] Description of Figure Numbers:
[0039] Label name Label name 1 Transfer substrate 3 Cathode Catalytic Layer 21 First carrier layer 4 Anode Catalytic Layer 22 Second carrier layer 5 Proton Exchange Membrane
[0040] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0042] In addition, the meaning of "and / or" appearing in the full text includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or a solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0043] At present, the commonly used processes for loading the catalyst layer on the PEM include ultrasonic spraying and transfer. Among them, the transfer method is to first coat the catalyst on the surface of the transfer substrate and then transfer it to the PEM. It has the advantages of high yield, no swelling, and low pollution. However, when the catalyst slurry is coated on the transfer substrate, it is easy to have uneven catalyst loading. In addition, since the catalyst slurry contains a binder, there is a certain adhesion between the catalyst layer and the transfer substrate, which often results in incomplete transfer of the catalyst layer or even transfer failure during the transfer process. The above two situations will lead to unstable quality of the final catalyst layer and low yield, thus limiting the large-scale production of membrane electrodes for water electrolysis.
[0044] In view of this, the present invention provides a method for preparing a membrane electrode for water electrolysis. In one embodiment, the method for preparing a membrane electrode for water electrolysis comprises the following steps:
[0045] Step S10 , disposing a first carrier layer 21 on an upper surface of a transfer substrate 1 .
[0046] Step S20 , disposing a second carrier layer 22 on the upper surface of another transfer substrate 1 .
[0047] The first support layer 21 includes a high molecular polymer, and the second support layer 22 includes a high molecular polymer. For ease of description, when describing the common features of the first support layer 21 and the second support layer 22, they are collectively referred to as support layers hereinafter, and when describing the common features of the cathode catalyst layer 3 and the anode catalyst layer 4, they are collectively referred to as catalyst layers hereinafter.
[0048] By setting a carrier layer between the transfer substrate 1 and the catalytic layer, direct contact between the transfer substrate 1 and the catalytic layer is avoided, so that the catalytic layer can be completely transferred during transfer, the transfer efficiency is high, and the quality of the transferred catalytic layer is stable; polymer is a material with high surface tension, so the prepared carrier layer has a larger surface tension than the transfer substrate 1, and is easier to be infiltrated by the catalyst slurry, thereby improving the load uniformity of the catalytic layer, which is beneficial to the improvement of the membrane electrode performance and service life; in addition, polymer is a soluble material, so the residual carrier layer on the membrane electrode can be removed by solvent dissolution, avoiding the negative impact of the residual carrier layer on the membrane electrode performance.
[0049] In this embodiment, the transfer substrate 1 is a sheet-like film. Further, the material of the transfer substrate 1 is at least one of polytetrafluoroethylene (PTFE), fluorinated ethylene propylene copolymer (FEP), perfluoroalkoxy copolymer (PFA), polyvinylidene fluoride (PVDF), and ethylene-tetrafluoroethylene copolymer (ETFE).
[0050] It should be noted that, in other embodiments of the present invention, step S20 may also be performed before step S10, or step S20 and step S10 may be performed simultaneously. It is only necessary to complete the preparation of the first carrier layer 21 and the second carrier layer 22 before the next operation (i.e., before step S30, complete step S10; before step S40, complete step S20). Figure 1 In this embodiment, step S10 and step S20 are performed simultaneously.
[0051] The material of the first carrier layer 21 includes a polymer. The present invention does not limit the specific type of the polymer, as long as it can be dissolved in water or an organic solvent under normal conditions. Preferably, the polymer is a water-soluble polymer. In this way, in the subsequent treatment process, only water needs to be added to dissolve the carrier layer, thereby achieving the purpose of removal, which is more environmentally friendly. Furthermore, the first carrier layer 21 includes at least one of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polymethyl pyrrolidone (PVP), polyacrylamide (PAM), and polyacrylic acid (PAA).
[0052] The material of the second carrier layer 22 includes a high molecular polymer. Based on the same reasons as the first carrier layer 21, preferably, the material of the second carrier layer 22 includes at least one of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polymethylpyrrolidone (PVP), polyacrylamide (PAM), and polyacrylic acid (PAA).
[0053] The materials of the first carrier layer 21 and the second carrier layer 22 may be the same or different. In order to facilitate operation and control the hot pressing conditions, in this embodiment, the materials of the first carrier layer 21 and the second carrier layer 22 are the same, so that step S10 and step S20 can be combined into one step, that is, the carrier layer is arranged on the transfer substrate.
[0054] The present invention does not limit the specific arrangement of the carrier layer on the transfer substrate 1. In the present embodiment, it is achieved by any one of the following two methods: (1) cutting a polymer film of the same size and attaching the film to the surface of the transfer substrate 1; (2) preparing a carrier layer slurry by dispersing or dissolving the polymer in a solvent, coating the slurry on the surface of the transfer substrate 1 and drying it.
[0055] Step S30 , disposing a cathode catalyst layer 3 on the first carrier layer 21 .
[0056] In a specific implementation, the cathode catalyst slurry is coated on the upper surface of the first carrier layer 21 and then dried to obtain the cathode catalyst layer 3 .
[0057] Wherein, the cathode catalyst slurry comprises a cathode catalyst, a dispersant and a binder. Further, the cathode catalyst comprises Pt / C. In another embodiment, the dispersant comprises at least one of water, ethanol, isopropanol and n-propanol. In another embodiment, the binder comprises a perfluorosulfonic acid resin solution. Preferably, in the cathode catalyst slurry, the cathode catalyst concentration is 2 to 20 mg / mL, and the mass of the binder is 20 to 50% of the mass of the cathode catalyst.
[0058] In order to improve the catalytic performance of the prepared membrane electrode, preferably, the cathode catalyst loading of the cathode catalyst layer 3 is 0.5-5 mg·cm -2 Furthermore, the cathode catalyst slurry is applied by any one of scraping, brushing and screen printing. In addition, the drying temperature is 50 to 90°C.
[0059] Step S40: disposing an anode catalyst layer on the second carrier layer.
[0060] Specifically, the anode catalyst slurry is coated on the surface of the second carrier layer 22 and then dried to obtain the anode catalyst layer 4 .
[0061] The present invention does not limit the specific drying temperature. In this embodiment, the drying temperature is 50-90° C., so that the drying speed is appropriate.
[0062] Wherein, the anode catalyst slurry includes an anode catalyst, a dispersant and a binder. In one embodiment, the anode catalyst includes iridium dioxide (IrO2). In another embodiment, the dispersant includes at least one of water, ethanol, isopropanol and n-propanol. In another embodiment, the binder includes a perfluorosulfonic acid resin solution. Preferably, in the anode catalyst slurry, the anode catalyst concentration is 2 to 20 mg / mL, and the mass of the binder is 20 to 50% of the mass of the cathode catalyst.
[0063] In order to improve the catalytic performance of the prepared membrane electrode, preferably, the anode catalyst loading on the second carrier layer 22 is 0.5-5 mg·cm -2 Furthermore, the method of applying the anode catalyst slurry includes any one of scraping, brushing and screen printing.
[0064] It should be noted that, in other embodiments of the present invention, step S40 may also be performed before step S30, or step S30 and step S40 may be performed simultaneously, and only need to be completed before the next operation (ie, before step S50). Figure 1 In this embodiment, step S30 and step S40 are performed simultaneously.
[0065] Step S50, placing the cathode catalyst layer 3 and the anode catalyst layer 4 on both sides of the proton exchange membrane 5 respectively, and making the cathode catalyst layer 3 contact the proton exchange membrane 5, and the anode catalyst layer 4 contact the proton exchange membrane 5, and obtaining a composite membrane through hot pressing treatment.
[0066] Through hot pressing treatment, the anode catalyst layer 4 and the cathode catalyst layer 3 are respectively transferred to the two sides of the proton exchange membrane 5. If the temperature, time or pressure of hot pressing is too high, the structure of the proton exchange membrane 5 or the catalyst layer will be damaged. If it is too low, it will lead to incomplete transfer of the catalyst layer or even transfer failure. In this embodiment, the hot pressing temperature of the hot pressing treatment is 90-140°C, the hot pressing pressure is 0.2-5.0MPa, and the hot pressing time is 1-10min. In this way, not only can the catalyst layer be completely transferred, but also the structure of the proton exchange membrane 5 or the catalyst layer will not be damaged.
[0067] Step S60: placing the composite membrane in a solvent to dissolve the first carrier layer 21 and the second carrier layer 22 in the solvent to obtain a membrane electrode for water electrolysis.
[0068] In this step, the first carrier layer 21 and the second carrier layer 22 are removed, thereby preventing the residual carrier layer from having a negative impact on the membrane electrode performance. The present invention designs the material of the carrier layer, so that the composite membrane is placed in a solvent and then taken out to remove the first carrier layer 21 and the second carrier layer 22, and the operation is simple.
[0069] The present invention does not limit the specific selection of the solvent, as long as it can dissolve the first carrier layer 21 and the second carrier layer 22. In this embodiment, since the first carrier layer 21 and the second carrier layer 22 are both made of water-soluble polymers, the solvent is water.
[0070] In summary, the preparation method of the membrane electrode for water electrolysis provided by the present invention is simple to operate, green and environmentally friendly, and the prepared membrane electrode for water electrolysis has good performance, long service life, stable quality, high yield rate, and is suitable for large-scale production.
[0071] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0072] The formulas of the cathode catalyst slurry and the anode catalyst slurry in Examples 1-4 are given below:
[0073] Cathode catalyst slurry: IrO2 catalyst and 5wt% perfluorosulfonic acid resin solution are uniformly dispersed in a dispersant with a volume ratio of water and ethanol of 1:1. The IrO2 content is 10mg·mL -1 , the mass of perfluorosulfonic acid resin is 40% of the mass of IrO2;
[0074] Anode catalyst slurry: 40wt% Pt / C catalyst and 5wt% perfluorosulfonic acid resin solution are uniformly dispersed in a dispersant with a volume ratio of water to ethanol of 1:1. The content of 40wt% Pt / C is 10mg·mL -1 , the mass of perfluorosulfonic acid resin is 40% of the mass of 40wt% Pt / C.
[0075] Example 1
[0076] (1) cutting a 50 mm × 50 mm PTFE film as a transfer substrate, and then cutting a 50 mm × 50 mm polyvinyl alcohol film and attaching it to the surface of the transfer substrate to obtain a carrier layer;
[0077] (2) Take a transfer substrate with a carrier layer (i.e., the first carrier layer) and apply the cathode catalyst slurry to the surface of the carrier layer by brushing. Heat and dry at 70°C to obtain a cathode catalyst layer, wherein the cathode catalyst loading is 1 mg cm -2 ;
[0078] (3) Take another transfer substrate with a carrier layer (i.e., the second carrier layer) and apply the anode catalyst slurry to the surface of the carrier layer by brushing, and heat and dry at 70°C to obtain an anode catalyst layer, wherein the anode catalyst loading is 2 mg cm -2 ;
[0079] (4) cutting a 60 mm × 60 mm Nafion 117 proton exchange membrane, placing it between a transfer substrate provided with a cathode catalyst layer and a transfer substrate provided with an anode catalyst layer, and hot pressing at 130° C. and 1.0 MPa for 3 min to obtain a composite membrane;
[0080] (5) Soaking the hot-pressed composite membrane structure in deionized water for 30 minutes to remove the carrier layer and obtain a membrane electrode for water electrolysis.
[0081] The membrane electrode for water electrolysis prepared in this example was placed under a scanning electron microscope for observation, and the results are as follows: Figure 2 As shown. Figure 2 It can be seen that the cathode catalyst layer and the anode catalyst layer on the membrane electrode have good uniformity, which means that when the catalyst slurry is coated on the carrier layer, the loading uniformity is good and the transfer is complete during the transfer process.
[0082] Example 2
[0083] (1) Cut a 80 mm × 80 mm PFA film as a transfer substrate, dissolve 5 g of polymethylpyrrolidone in 100 mL of deionized water to prepare a carrier layer slurry, and apply the slurry on the surface of the PTFE film by scraping and drying to obtain a carrier layer;
[0084] (2) Take a transfer substrate with a carrier layer (i.e., the first carrier layer) and apply the cathode catalyst slurry on the surface of the carrier layer by scraping, and heat and dry at 90°C to obtain a cathode catalyst layer, wherein the cathode catalyst loading is 0.5 mg cm -2 ;
[0085] (3) Take another transfer substrate with a carrier layer (i.e., the second carrier layer), apply the anode catalyst slurry on the surface of the carrier layer, and heat and dry it at 90° C. to obtain an anode catalyst layer, wherein the anode catalyst loading is 1.5 mg cm -2 ;
[0086] (4) cutting a 90 mm×90 mm Nafion 117 proton exchange membrane, placing it between a transfer substrate provided with a cathode catalyst layer and a transfer substrate provided with an anode catalyst layer, and hot pressing at 120° C. and 1.5 MPa for 2 min to obtain a composite membrane;
[0087] (5) Soaking the hot-pressed composite membrane structure in deionized water for 30 minutes to remove the residual carrier layer components and obtain a membrane electrode for water electrolysis.
[0088] Example 3
[0089] (1) Cut a 50 mm × 50 mm FEP film as a transfer substrate, dissolve 5 g of polyacrylamide in 100 mL of deionized water to prepare a carrier layer slurry, apply the slurry to the surface of the PTFE film and dry it to obtain a carrier layer;
[0090] (2) Take a transfer substrate with a carrier layer (i.e., the first carrier layer) and apply the cathode catalyst slurry on the surface of the carrier layer by brushing. Heat and dry at 50°C to obtain a cathode catalyst layer, wherein the cathode catalyst loading is 2 mg cm -2 ;
[0091] (3) Take another transfer substrate with a carrier layer (i.e., the second carrier layer) and apply the anode catalyst slurry to the surface of the carrier layer by brushing, and heat and dry at 50° C. to obtain an anode catalyst layer, wherein the anode catalyst loading is 4 mg cm -2 ;
[0092] (4) cutting a 60 mm×60 mm Nafion 117 proton exchange membrane, placing it between a transfer substrate provided with a cathode catalyst layer and a transfer substrate provided with an anode catalyst layer, and hot pressing at 90° C. and 5.0 MPa for 5 min to obtain a composite membrane;
[0093] (5) Soaking the hot-pressed composite membrane structure in deionized water for 30 minutes to remove the residual carrier layer components and obtain a membrane electrode for water electrolysis.
[0094] Example 4
[0095] (1) using a PVDF film with a size of 50 mm×50 mm as a transfer substrate, and attaching a polyethylene oxide film with a size of 50 mm×50 mm to the surface of the transfer substrate to obtain a first carrier layer;
[0096] (2) using a PVDF film with a size of 50 mm×50 mm as a transfer substrate, and attaching a polyacrylic acid film with a size of 50 mm×50 mm to the surface of the transfer substrate to obtain a second carrier layer;
[0097] (3) The cathode catalyst slurry was brushed onto the surface of the first carrier layer and heated and dried at 60° C. to obtain a cathode catalyst layer, wherein the cathode catalyst loading was 5 mg cm -2 ;
[0098] (4) Applying the anode catalyst slurry to the surface of the second support layer, heating and drying at 60° C. to obtain an anode catalyst layer, wherein the anode catalyst loading is 4 mg cm -2 ;
[0099] (5) cutting a 60 mm × 60 mm Nafion 117 proton exchange membrane, placing it between a transfer substrate provided with a cathode catalyst layer and a transfer substrate provided with an anode catalyst layer, and hot pressing for 10 min at 100° C. and 0.2 MPa to obtain a composite membrane;
[0100] (6) The hot-pressed composite membrane structure is immersed in deionized water for 30 minutes to remove the remaining components of the first carrier layer and the second carrier layer to obtain a membrane electrode for water electrolysis.
[0101] Example 5
[0102] Except that the hot pressing step of step (4) is modified to: hot pressing for 1 min under the conditions of 140° C. and 2 MPa to obtain a composite membrane, the remaining steps are the same as those of Example 1.
[0103] Example 6
[0104] In addition to modifying the cathode catalyst loading to 2 mg cm -2 , the anode catalyst loading is 5 mg cm -2 , the remaining steps are the same as those in Example 1.
[0105] Comparative Example 1
[0106] Except that the carrier layer is not provided, the remaining steps are the same as those in Example 1, that is, the steps are as follows:
[0107] (1) Cut 50 mm × 50 mm PTFE film as the transfer substrate;
[0108] (2) Take a piece of transfer substrate, apply the cathode catalyst slurry on the surface of the carrier layer, and heat and dry it at 70°C to obtain a cathode catalyst layer, wherein the cathode catalyst loading is 1 mg cm -2 ;
[0109] (3) Take another transfer substrate, apply the anode catalyst slurry to the surface of the carrier layer, and heat and dry it at 70°C to obtain an anode catalyst layer, wherein the anode catalyst loading is 2 mg cm -2 ;
[0110] (4) cutting a 60 mm × 60 mm Nafion 117 proton exchange membrane, placing it between a transfer substrate provided with a cathode catalyst layer and a transfer substrate provided with an anode catalyst layer, and hot pressing at 130° C. and 1.0 MPa for 3 min to obtain a composite membrane;
[0111] (5) Soaking the hot-pressed composite membrane structure in deionized water for 30 minutes to remove the carrier layer and obtain a membrane electrode for water electrolysis.
[0112] (I) Investigation of transfer effect
[0113] The anode catalyst layer of the membrane electrode for water electrolysis prepared in Example 1 and Comparative Example 1 was observed under an electron microscope. The results are as follows: Figure 3 shown.
[0114] Depend on Figure 3 It can be seen that the anode catalyst layer in Example 1 is uniformly transferred to the surface of the proton exchange membrane, while the anode catalyst layer in Comparative Example 1 has obvious uneven transfer on the right side.
[0115] (II) Catalytic performance test
[0116] The membrane electrodes for water electrolysis obtained in Example 1 and Comparative Example 1 were placed in the SPE water electrolysis test system for testing. The test conditions were a constant current density of 2 A·cm -2 , temperature 80℃, membrane electrode working area 20cm 2 Specific test results are as follows: Figure 4 shown.
[0117] Depend on Figure 4 It can be seen that the membrane electrode in Example 1 has a starting voltage of 1.85 V, which has a lower overpotential than that of Comparative Example 1 without a carrier layer. At the same time, in subsequent tests, the membrane electrode voltage in Example 1 increases more slowly, reflecting better water electrolysis catalytic performance and stability.
[0118] (III) Quality stability test
[0119] The 10 membrane electrodes for water electrolysis prepared in Example 1 and Comparative Example 1 were placed in the SPE water electrolysis test system to test their initial working voltage. The test conditions were a constant current density of 2 A·cm -2 , temperature 80℃, membrane electrode working area 20cm 2 The test results are shown in Table 1 below. Table 1 Quality stability test results
[0120]
[0121] It can be seen from Table 1 that among the membrane electrode samples prepared in Example 1, the initial working voltage of all samples is below 1.90 V, and the sample quality is relatively stable. Among the membrane electrode samples prepared in Comparative Example 1, the voltage of samples No. 4 and No. 10 is significantly higher, the voltage fluctuation between samples is more obvious, and the sample quality stability is poor.
[0122] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A method for preparing a membrane electrode for water electrolysis, characterized in that: The following steps are involved: Disposing a first carrier layer on an upper surface of a transfer substrate; Disposing a second carrier layer on the upper surface of another transfer substrate; Disposing a cathode catalyst layer on the first carrier layer; Disposing an anode catalyst layer on the second carrier layer; The cathode catalyst layer and the anode catalyst layer are respectively placed on both sides of the proton exchange membrane, and the cathode catalyst layer is in contact with the proton exchange membrane, and the anode catalyst layer is in contact with the proton exchange membrane, and subjected to hot pressing treatment to obtain a composite membrane; placing the composite membrane in a solvent to dissolve the first carrier layer and the second carrier layer in the solvent to obtain a membrane electrode for water electrolysis; Wherein, the material of the first carrier layer includes at least one of polyvinyl alcohol, polyethylene oxide, polymethylpyrrolidone, polyacrylamide and polyacrylic acid; The material of the second carrier layer includes at least one of polyvinyl alcohol, polyethylene oxide, polymethyl pyrrolidone, polyacrylamide and polyacrylic acid.
2. The method for preparing a membrane electrode for water electrolysis according to claim 1, wherein: The material of the transfer substrate includes at least one of polytetrafluoroethylene, fluorinated ethylene-propylene copolymer, perfluoroalkoxy copolymer, polyvinylidene fluoride and ethylene-tetrafluoroethylene copolymer.
3. The method for preparing a membrane electrode for water electrolysis according to claim 1, wherein: The step of providing a cathode catalyst layer on the first carrier layer comprises: The cathode catalyst slurry is coated on the upper surface of the first carrier layer and then dried to obtain a cathode catalyst layer, wherein the cathode catalyst slurry includes a cathode catalyst, a dispersant and a binder.
4. The method for preparing a membrane electrode for water electrolysis according to claim 3, wherein: The cathode catalyst comprises Pt / C; and / or, The dispersant comprises at least one of water, ethanol, isopropanol and n-propanol; and / or, The drying temperature of the drying is 50 to 90° C.; and / or, The cathode catalyst slurry may be applied by any one of blade coating, brush coating and screen printing.
5. The method for preparing a membrane electrode for water electrolysis according to claim 3, characterized in that: The cathode catalyst loading on the cathode catalyst layer is 0.5 to 5 mg cm -2 .
6. The method for preparing a membrane electrode for water electrolysis according to claim 1, characterized in that: The step of providing an anode catalyst layer on the second carrier layer comprises: The cathode catalyst slurry is coated on the upper surface of the first carrier layer and dried to obtain a cathode catalyst layer, wherein the anode catalyst slurry includes an anode catalyst, a dispersant and a binder.
7. The method for preparing a membrane electrode for water electrolysis according to claim 6, characterized in that: The anode catalyst comprises iridium dioxide; and / or, The dispersant comprises at least one of water, ethanol, isopropanol and n-propanol; and / or, The drying temperature of the drying is 50 to 90° C.; and / or, The method of applying the anode catalyst slurry includes any one of blade coating, brush coating and screen printing.
8. The method for preparing a membrane electrode for water electrolysis according to claim 6, characterized in that: The anode catalyst loading on the anode catalyst layer is 0.5 to 5 mg cm -2 .
9. The method for preparing a membrane electrode for water electrolysis according to claim 1, characterized in that: In the hot pressing step, the hot pressing temperature is 90-140° C., the hot pressing pressure is 0.2-5.0 MPa, and the hot pressing time is 1-10 min.
Citation Information
Patent Citations
Fuel cell membrane electrode and preparation method thereof
CN113381045A